Reduced (1)H-NMR visibility of creatine in isolated rat hearts. - Schneider, J; Fekete, E; Weisser, A; Neubauer, S; von Kienlin, M (2000)
The aim of this study was to measure the concentration of creatine in Langendorff perfused rat hearts, both by quantitative (1)H-MRS and by high-pressure liquid chromatography (HPLC). First, the relaxation times and other parameters affecting absolute quantification by MRS were determined. At 11.75 T, the relaxation times of myocardial creatine were T(1) = 1.1+/-0.29 sec (mean +/- SD, n = 5) and T(2) = 56.4+/-6.2 ms (n = 9). In phantom experiments the MRS measurements gave accurate values for the known relative concentrations of the detected substances. In glucose-perfused rat hearts, the creatine concentration measured by HPLC was 14.2+/-1.9 mmol/kg wet weight (n = 8), in good agreement with literature values. The (1)H-MRS measurements, however, resulted in creatine concentrations of only approximately 60% of this value. The application of CHESS-pulses for water suppression led to a further 30% reduction of the creatine MRS signal. These results indicate a reduced (1)H-NMR visibility of creatine in the myocardium, which suggests a compartmentation of myocardial creatine into various pools.